2000
DOI: 10.1016/s0002-9440(10)64996-6
|View full text |Cite
|
Sign up to set email alerts
|

The Fn14 Immediate-Early Response Gene Is Induced During Liver Regeneration and Highly Expressed in Both Human and Murine Hepatocellular Carcinomas

Abstract: Polypeptide growth factors stimulate mammalian cell proliferation by binding to specific cell surface receptors. This interaction triggers numerous biochemical responses including the activation of protein phosphorylation cascades and the enhanced expression of specific genes. We have identified several fibroblast growth factor (FGF)-inducible genes in murine NIH 3T3 cells and recently reported that one of them, the FGF-inducible 14 (Fn14) immediate-early response gene, is predicted to encode a novel, cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
190
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(195 citation statements)
references
References 36 publications
5
190
0
Order By: Relevance
“…We have found that Fn14 is expressed on erythroid precursor cells, which are characterized by a high proliferative potential. This finding is consistent with previous reports on Fn14 expression in actively dividing tissues, such as the regenerating liver and injured vessel wall (27,45), thus suggesting a general role for Fn14 in balancing cell expansion. TWEAK mRNA is expressed in erythroid precursor cells until the latest maturation stages, whereas TWEAK protein is present at low levels on the plasma membrane.…”
Section: Discussionsupporting
confidence: 93%
“…We have found that Fn14 is expressed on erythroid precursor cells, which are characterized by a high proliferative potential. This finding is consistent with previous reports on Fn14 expression in actively dividing tissues, such as the regenerating liver and injured vessel wall (27,45), thus suggesting a general role for Fn14 in balancing cell expansion. TWEAK mRNA is expressed in erythroid precursor cells until the latest maturation stages, whereas TWEAK protein is present at low levels on the plasma membrane.…”
Section: Discussionsupporting
confidence: 93%
“…The TWEAK receptor turned out to be a fibroblast growth factor-inducible 14-kDa protein, Fn14, which was originally identified by a differential display approach to search for growth factor-inducible molecules in murine NIH3T3 fibroblasts (14,15). Fn14 is a distantly related TNFR family member, which contains only one cysteine-rich domain in the extracellular region and a TNFR-associated factor (TRAF) binding domain, but not the DD, in the cytoplasmic region (13).…”
Section: Embers Of the Tnf Family Play Important Roles In Reg-mentioning
confidence: 99%
“…13 Although TWEAK is almost ubiquitously expressed in adult tissues, including the liver, its cognate receptor is barely detectable in hepatic tissue except during injury and repair. Feng et al 14 reported rapid induction of Fn14 expression during the early phases of regeneration following partial hepatectomy. The authors also investigated liver cancer-derived cell lines, and interestingly, Fn14 overexpression was mainly found in the poorly differentiated lines; this hinted at possible involvement in progenitor cells.…”
mentioning
confidence: 99%